Integrating environmental social and governance values into higher education curriculum - Alenezi, Mamdouh; Alanazi, Fayez (International Journal of Evaluation and Research in Education (IJERE), 2024)
This paper proposes a framework for integrating Environmental, Social, and Governance (ESG) principles into higher education institutions. The framework consists of six components: curriculum integration, research and innovation, campus operations, community engagement, leadership and governance, and assessment and reporting. Each component is supported by eight implementation strategies that provide practical guidance for institutions looking to advance their sustainability efforts. The proposed framework is informed by a literature review that highlights the importance of ESG considerations in higher education, the challenges and opportunities associated with integrating sustainability into higher education institutions, and the role that institutions can play in promoting sustainable development. The framework is also supported by case studies that illustrate how institutions have successfully implemented sustainability initiatives and the benefits that have accrued as a result. The proposed framework has the potential to make a significant contribution to the advancement of sustainability in higher education institutions and promote sustainable development in the broader community. It is hoped that the framework will be useful to institutions, policymakers, and other stakeholders interested in promoting sustainability in higher education.